A Preliminary Study of Genetic Variation of Selected Species of a Lowland Forest at Ayer Hitam Forest Reserve, Selangor - Ab Shukor, Nor Aini (Universiti Putra Malaysia Press, 1999)
A preliminary study of the extent and pattern of genetic variation of 10 selected species (Shorea parvifolia, Shorea macroptera, Shorea acuminata, Shorea leprosula, Hopea beccariana, Dipterocarpus crinitus, Endospermum malaccensis, Artocarpus elasticus, Palaquium gutta and Macaranga gigantea at Ayer Hitam Forest Reserve was carried out using the horizontal starch gel electrophoresis. Analysis of eight enzymes indicated that they were coded by 9 to 12 loci. Levels of polymorphism and mean of expected heterozygosities of these species ranged from 0.9 to 1.0 and from 0.454 (S. leprosula) to 0.602 (H. beccariana) respectively.